Novel Espin Actin-Bundling Proteins Are Localized to Purkinje Cell Dendritic Spines and Bind the Src Homology 3 Adapter Protein Insulin Receptor Substrate p53 - Sekerková, Gabriela (Society for Neuroscience, 2003)
We identified a group of actin-binding–bundling proteins that are expressed in cerebellar Purkinje cells (PCs) but are not detected in other neurons of the CNS. These proteins are novel isoforms of the actin-bundling protein espin that arise through the use of a unique site for transcriptional initiation and differential splicing. Light and electron microscopic localization studies demonstrated that these espin isoforms are enriched in the dendritic spines of PCs. They were detected in the head and neck and in association with the postsynaptic density (PSD) of dendritic spines in synaptic contact with parallel or climbing fibers. They were also highly enriched in PSD fractions isolated from cerebellum. The PC espins efficiently bound and bundled actin filaments in vitro, and these activities were not inhibited by Ca(2+). When expressed in transfected neuronal cell lines, the PC espins colocalized with actin filaments and elicited the formation of coarse cytoplasmic actin bundles. The insulin receptor substrate p53 (IRSp53), an Src homology 3 (SH3) adapter protein and regulator of the actin cytoskeleton, was identified as an espin-binding protein in yeast two-hybrid screens. Cotransfection studies and pull-down assays showed that this interaction was direct and required the N-terminal proline-rich peptide of the PC espins. Thus, the PC espins exhibit the properties of modular actin-bundling proteins with the potential to influence the organization and dynamics of the actin cytoskeleton in PC dendritic spines and to participate in multiprotein complexes involving SH3 domain-containing proteins, such as IRSp53.